Lymphocytic esophagitis as a cause of dysphagia: a case report and brief literature review - Perez-Valenzuela, Javier (2026)
Lymphocytic esophagitis (LyE) is a chronic inflammatory condition of the esophagus with a prevalence of ~0.1% among esophageal biopsies. The main clinical manifestations are dysphagia, heartburn, and chest pain; some endoscopic findings includes rings, strictures, and furrows. A 63-year-old woman with Sjögren syndrome and treated hypothyroidism presented with a 1-year history of progressive solid-food dysphagia and 4-kg weight loss. Endoscopy and a barium esophagogram revealed a proximal esophageal web, which was treated with endoscopic dilation. A follow-up esophagogastroduodenoscopy showed esophageal rings and luminal narrowing. Biopsies confirmed LyE. She was treated with esomeprazole with good clinical response. LyE is a recently described entity in which clinicopathologic correlations are not always straightforward. Given overlap in symptoms and endoscopic features, eosinophilic esophagitis is the principal differential diagnosis. Management options include proton-pump inhibitors, swallowed topical corticosteroids, and esophageal dilation for fixed strictures. Clear, evidence-based clinical guidelines are still lacking.